Norms in private bankruptcy: the 'London Approach' to the resolution of financial distress - Armour, J; Deakin, S (Taylor and Francis, 2001)
In recent years law and economics scholarship has expanded its frame of reference to incorporate the role of social norms in shaping the incentives of actors. This shift in perspective has yet to filter through to the literature on insolvency, which has to date concentrated on the role of legal rules in resolving financial distress. This article presents qualitative findings on how financial distress is resolved amongst creditors of large UK firms. Such restructurings proceed according to an informal set of market norms known collectively as the “London Approach”. The article suggests that regulatory pressure applied by the Bank of England may have been critical in “seeding” the market norms. It also examines the prospects for the London Approach's future in light of changes in the financial environment brought about by globalisation. The article points the way towards an incorporation into insolvency law scholarship of the role played by social norms.